Recovering Rare-Earth Magnets from Wind Turbines—A Potential Analysis for Germany - Anton Jäger; Zoe Chunyu Miao; Steffi Weyand (Energies)
Wind power forms the major contributor to Germany’s goal of transforming the energy sector and becoming climate-neutral until 2045. The increasing installation of wind turbines comes with an increasing demand for rare-earth elements, especially neodymium, praseodymium and dysprosium, to produce high-performing magnets. However, these elements are considered to be critical raw materials because of their supply risk and economic importance. The European Commission aims to ensure supply chain resilience by improving the circularity of these critical raw materials. After an average of 20 years, wind turbines transition into their End-of-Life phase. This work aims to map the present and future potential of NdFeB magnets used in wind turbines in Germany to be introduced into a circular economy resulting in material amounts of potentially recycled magnets and secondary rare-earth elements considering different potential End-of-Life pathways.